2019
DOI: 10.3390/antibiotics8030087
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Geldanamycin Biosynthesis by Cluster-Situated Transcription Factors and the Master Regulator PhoP

Abstract: Geldanamycin and the closely related herbimycins A, B, and C are benzoquinone-type ansamycins with antitumoral activity. They are produced by Streptomyces hygroscopicus var. geldanus, Streptomyces lydicus and Streptomyces autolyticus among other Streptomyces strains. Geldanamycins interact with the Hsp-90 chaperone, a protein that has a key role in tumorigenesis of human cells. Geldanamycin is a polyketide antibiotic and the polyketide synthase contain seven modules organized in three geldanamycin synthases ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…The PhoR-PhoP system is conserved in all Streptomyces and most other sequenced actinomycetes ( Barreiro and Martínez-Castro, 2019 ). Many studies have demonstrated that this system plays an important regulatory role in cellular differentiation and secondary metabolite biosynthesis in actinomycetes ( Sola-Landa et al., 2003 , 2005 , 2013 ; Martín et al., 2019 ). In another system that senses and responds to phosphate, the sensor kinase SenX3 and the response regulator RegX3 were first identified and have been well studied in Mycobacterium ( Namugenyi et al., 2017 ; Rifat et al., 2014 ; Park et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PhoR-PhoP system is conserved in all Streptomyces and most other sequenced actinomycetes ( Barreiro and Martínez-Castro, 2019 ). Many studies have demonstrated that this system plays an important regulatory role in cellular differentiation and secondary metabolite biosynthesis in actinomycetes ( Sola-Landa et al., 2003 , 2005 , 2013 ; Martín et al., 2019 ). In another system that senses and responds to phosphate, the sensor kinase SenX3 and the response regulator RegX3 were first identified and have been well studied in Mycobacterium ( Namugenyi et al., 2017 ; Rifat et al., 2014 ; Park et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of LAL-type regulatory factor samR in Streptomyces ambofaciens activated a 150 kb cryptic gene cluster, and promoted the discovery of a glycosylated macrolide product with anti-cancer activity (Laureti et al, 2011). Similarly, LAL-type transcriptional regulators of GdmRI and GdmRII in S. hygroscopicus are positive to geldanamycin biosynthesis (Martin et al, 2019). Furthermore, the LAL-like 63-amino acid protein AfsS and its homologs have been shown to relate closely with the induction of avermectin in S. avermitilis (Lee et al, 2000), pikromycin in S. venezuelae (Maharjan et al, 2009), and DXR in S. peucetius (Parajuli et al, 2005).…”
Section: Activation Of the Cryptic Gene Clusters By Manipulation Of Tmentioning
confidence: 99%
“…avermitilis, phoP negatively regulates the avermectin production, whereas phoP does not affect the production of oligomycin . The deletion of phoP appears to strongly inhibit cell growth but increase the production of geldanamycin in Streptomyces hygroscopicus . Moreover, the filipin production in Streptomyces filipinensis was greatly improved by deleting phoP .…”
Section: Discussionmentioning
confidence: 98%
“…These results indicated that phoP may participate in the regulation of secondary metabolites in S. lomondensis S015 as reported elsewhere. 29,31 To investigate the effects of phoP on CFTHP biosynthesis, it was disrupted in S. lomondensis S015 through a 466 bp internal deletion, as shown in Figure 4A. Also, the resulting strain S015ΔphoP was confirmed by PCR amplification (Figure 4B).…”
Section: Purification and Structural Characterization Of Novelmentioning
confidence: 99%
See 1 more Smart Citation